Inheriting Leadership: Analyzing Successor Traits in Coimbatore's Family Businesses - Indira Priyadharshini B (Future Science, 2025)
Succession in family businesses is a critical process that influences the longevity and success of these enterprises. This study examines the traits necessary for effective successors in family businesses, focusing specifically on the Coimbatore district, a region known for its dynamic industrial landscape. Through a combination of qualitative and quantitative methods, including surveys and interviews with current family business leaders and potential successors, this research identifies key characteristics such as leadership skills, strategic thinking, and interpersonal abilities. The findings highlight the importance of balancing traditional values with modern business acumen to ensure seamless transitions and sustained business growth. This study provides valuable insights for family business stakeholders in Coimbatore and similar regions, offering practical recommendations to facilitate successful leadership succession and enhance long-term business continuity.